2021
DOI: 10.3389/fendo.2020.593173
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Trabecular Bone Score in Patients With Active Endogenous Cushing’s Syndrome

Abstract: IntroductionThe impairment in bone microarchitecture and reduced bone quality are relevant mechanisms underlying the increased fracture risk in Cushing’s syndrome (CS). The trabecular bone score (TBS) is a relatively novel textural index of bone microarchitecture.PurposeThe objective of the study was to compare TBS, bone mineral density (BMD), and fracture risk in patients with endogenous CS to controls. We have investigated the association of TBS with anthropometric parameters and 25(OH) vitamin D concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In this context, TBS appears to be a valuable tool in assessing the bone status and estimating fracture risk in patients with glucocorticoid-induced osteoporosis. It has been shown that in patients with endogenous hypercortisolemia TBS values were significantly lower than in controls, moreover, subjects with Cushing`s syndrome with fractures had low TBS values ( 29 ). However, the effect of exogenous glucocorticoids on bone may be different, because it is modulated by various mechanisms at a tissue level, like variations in the expression and sensitivity of the glucocorticoid receptors (GRs), the action of transmembrane transporters, and enzymatic metabolism of glucocorticoids to more or less active forms by 11β-hydroxysteroid dehydrogenases (11β-HSDs) ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, TBS appears to be a valuable tool in assessing the bone status and estimating fracture risk in patients with glucocorticoid-induced osteoporosis. It has been shown that in patients with endogenous hypercortisolemia TBS values were significantly lower than in controls, moreover, subjects with Cushing`s syndrome with fractures had low TBS values ( 29 ). However, the effect of exogenous glucocorticoids on bone may be different, because it is modulated by various mechanisms at a tissue level, like variations in the expression and sensitivity of the glucocorticoid receptors (GRs), the action of transmembrane transporters, and enzymatic metabolism of glucocorticoids to more or less active forms by 11β-hydroxysteroid dehydrogenases (11β-HSDs) ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…TBS is correlated with trabecular bone volume, the number of trabeculae and their connectivity ( 28 ). It has been shown, that in patients with endogenous hypercortisolemia TBS was significantly lower than in control group and correlated with disease duration ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, compared to control subjects, TBS was reported to be lower in patients with diabetes (42,(57)(58)(59), primary hyperparathyroidism (60)(61)(62)(63)(64), acromegaly (65)(66)(67)(68), anorexia nervosa (69,70), hypercortisolism (71)(72)(73), primary aldosteronism (especially in women) (74), with prolonged GC exposure (75)(76)(77)(78)(79)(80)(81)(82)(83)(84), rheumatoid arthritis and rheumatic disease (85)(86)(87), aromatase inhibition (88), kidney transplant recipients (89), as well as in patients on hemodialysis (90,91). In differentiated thyroid carcinomas, TBS was found to be lower in patients receiving long-term suppressive doses of thyroid-stimulating hormone than in patients receiving shorter-term therapy (92)(93)(94).…”
Section: Tbs and Fracture Risk Prediction In Patients With Diabetes A...mentioning
confidence: 93%
“…Besides, cortisol can also improve recruitment of basic multicellular units in bone and then procuring the stimulation of bone turnover with the catabolic processes involved trabecular bone [8,9] . As a result, patients with hypercortisolism are prone to fracture despite normal or slightly lower BMD [10] . PHPT and hypercortisolism can directly or indirectly affect the PTH, which will also affect bone metabolism and bone quality, therefore, sex-, age-matched hypercortisolism patients were selected as a control group compared with PHPT patients.…”
Section: Introductionmentioning
confidence: 99%